2023
DOI: 10.17219/dmp/152181
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase-1, a novel link between periodontitis and ischemic heart disease: A case–control study

Abstract: Background. Periodontitis is a chronic inflammatory disease and might be a potential risk factor for ischemic heart disease (IHD). However, the link between periodontitis and atherosclerosis is not yet fully understood. Paraoxonase-1 (PON-1) is a new biomarker representing both anti-atherosclerotic and antioxidant activity, which also acts against dental biofilm formation and periodontitis. The possible contributing role of PON-1 in the relationship between periodontitis and atherosclerosis has not been studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Evidence for these mechanisms was revealed, for example, by Ghorbani et al, who demonstrated that the combination of ischemic heart disease and periodontitis is associated with a lower activity of Paraoxonase-1 (PON-1), a new biomarker representing both anti atherosclerotic and antioxidant activity [14]. Narendran et al assessed the myocardial strain among controlled hypertensive patients with periodontitis and showed that an increase in the periodontal inflamed surface area (PISA) score may cause mild alterations in the global longitudinal strain (GLS) score, which could indicate the possible influence of periodontitis on myocardial activity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for these mechanisms was revealed, for example, by Ghorbani et al, who demonstrated that the combination of ischemic heart disease and periodontitis is associated with a lower activity of Paraoxonase-1 (PON-1), a new biomarker representing both anti atherosclerotic and antioxidant activity [14]. Narendran et al assessed the myocardial strain among controlled hypertensive patients with periodontitis and showed that an increase in the periodontal inflamed surface area (PISA) score may cause mild alterations in the global longitudinal strain (GLS) score, which could indicate the possible influence of periodontitis on myocardial activity [15].…”
Section: Introductionmentioning
confidence: 99%